a) -3(5y-2) -1/2= -2(y+1/4)
- 15y + 6 - 1/2 = -2y - 1/2 | + 1/2 + 15y
6 = 13y | :13
6/13 = y
b) 3x/4-x/2+7=x+28/4
3/4x - 2/4x + 7 = x + 7
1/4x + 7 = x + 7 | -7
1/4x = x (równanie sprzeczne)
c) t- 2t-1/3=1/3(t-3)
-t - 1/3 = 1/3t - 1 | + t + 1
2/3 = 4/3 t | :4/3
2/3 * 3/4 = t
1/2 = t
d) 4(x-3/2) +3(2 1/2-x) = 3/4x-2
4x - 6 + 7 1/2 - 3x = 3/4x - 2
x + 1 1/2 = 3/4x - 2 | + x +2
3 1/2 = 7/4x | :7/4
7/2 * 4/7 = x
1/2 = x
e) 2x+4/4-x= - 3x-6/2
x + 1 = -3x -3 | + 1 + 3x
4x = -4 | :4
x = -1
Mam nadzieję że pomogłam i liczę na naj. ♥